The KIST in South Korea and the issues on the establishment of the V-KIST in Vietnam - Thang, Bui Tat (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
In order to make science and technology (S&T) to really play a core role in improving labor productivity and competitiveness of the economy, besides of clear identification and deep understanding of the position of S&T as “a top national focused policy”, the issues of the rational development of the hierarchy of scientific research institutions and especially the mechanisms for linking S&T to production, which are in line with market economy institutions, are very decisive. While establishing such mechanisms, South Korea successfully built the KIST model and expanded it into its entire S&T research system. Currently, the South Korean government has been helping Vietnam to build the V-KIST Institute following the model of South Korea’s KIST. During the implementation of the VKIST, what are the key issues that Vietnam should pay attention for to achieve the expected success? Code: 17042001